2017
DOI: 10.1016/j.vacuum.2017.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Ta/TaN/TaNx(Ag)y/TaN nanocomposite coating system and bio-response study for biomedical applications

Abstract: TaN(Ag) composited coatings are being investigated to improve biocompatibility of different biomedical devices due to the mechanical and chemical stability of TaN and bactericidal effect of silver nanoparticles. However, controlling the size, density, shape and especially the release of silver ions (Ag) into the surrounding medium becomes a challenge, since elevated levels of Ag could be cytotoxic. The aim of this work is to design and develop a new Ta/TaN/TaNx(Ag)y/TaN coating system, deposited by unbalanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 80 publications
3
11
0
Order By: Relevance
“…7 shows the water contact angle and the surface free energy of the Ti-6Al-4V and the deposited coatings. Here, it can be observed that both the TiN coating and the substrate used have hydrophobic behavior, according to the authors of the report [38], since the contact angle was greater than 90°. On the other hand, the HA-Ag coatings showed a greater water affinity, obtaining a significant reduction in the contact angle and presenting a hydrophilic character.…”
Section: Coatings Ti/n Ratio Ca/p Ratiosupporting
confidence: 51%
“…7 shows the water contact angle and the surface free energy of the Ti-6Al-4V and the deposited coatings. Here, it can be observed that both the TiN coating and the substrate used have hydrophobic behavior, according to the authors of the report [38], since the contact angle was greater than 90°. On the other hand, the HA-Ag coatings showed a greater water affinity, obtaining a significant reduction in the contact angle and presenting a hydrophilic character.…”
Section: Coatings Ti/n Ratio Ca/p Ratiosupporting
confidence: 51%
“…In the coating procedure by RDCMS technique, the nitrogen gas reacts under the electric field and acts as an anode, with extracted atoms from the cathode surface, so the coating is produced. RDCMS technique produces constant coatings 42,43 . Indeed, the continuity seems to coat the entire surface, making the coating with no holes.…”
Section: Resultsmentioning
confidence: 99%
“…RDCMS technique produces constant coatings. 42,43 Indeed, the continuity seems to coat the entire surface, making the coating with no holes. The images indicate the presence of small cavities inside the produced coating within the specimen having a content of 5.2% P N2 /P Ar (Figure 3A).…”
Section: Surface Characterizationmentioning
confidence: 99%
“…Ag cytotoxicity was evaluated by MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide) assay (Roche). mMSCs with a density of 10.000/cm 2 were seeded in culture plates with cell culture medium consisting of Dulbecco's Modified Eagle Medium (Invitrogen) supplemented with 10% fetal bovine serum and 1% penicillin/streptomycin at 37 °C and 5% CO2 for 24 h. After, this medium was replaced by culture medium containing AgCl, which was added to obtain Ag + concentrations from 0.06 to 14.64 mg/L, which were defined according to results registered for the Ag release assay and some reports in the literature [14,30]. Thereupon, an incubation for 72 h was carried out.…”
Section: Ag Cytotoxicity Testmentioning
confidence: 99%
“…mMSCs were seeded at a density of 5.000/cm 2 on the surface of the coatings and the substrate in cell culture medium at 37 °C and 5% CO2 for 3 and 24 h. After each culture, samples were washed, fixed and permeabilized as described in [30]. For the immunostaining procedure, samples were incubated in primary antibody anti-vinculin (Sigma) dil.…”
Section: Cell Adhesionmentioning
confidence: 99%